Validated Digital Pop Up Book Media for Indonesian Language Learning: Media Pop Up Book Digital Tervalidasi untuk Pembelajaran Bahasa Indonesia - Taqwa, Rachmat Alim; Haslinda, Haslinda; Akib, Tasrif (Academia Open, 2026)
General Background Indonesian language learning in elementary schools requires media that supports literacy, student engagement, and meaningful comprehension of narrative texts. Specific Background Folklore material in fourth-grade Indonesian language learning contains linguistic, moral, and cultural values, yet students often experience boredom and difficulty understanding long textual materials without visual and interactive support. Knowledge Gap Previous pop-up book studies have mostly focused on printed or manual media, while research on digital-based pop-up book media for Indonesian language folklore learning in elementary classrooms remains limited. Aims This study aimed to develop and examine the prototype, validity, practicality, and classroom results of digital-based pop-up book media for folklore material in fourth-grade Indonesian language learning. Results The developed product was a digital-based pop-up book media containing folklore material. Expert validation showed very valid results, with media expert validation reaching 96% and material expert validation reaching 92%. Practicality was confirmed through very good implementation observation, teacher response with an average score of 97, and student response reaching 89%. Student learning outcomes increased from a pretest mean of 69.54 to a posttest mean of 81.75, while learning motivation increased from 51.08 to 82.96. Novelty The study offers a digital pop-up book integrating interactive visual elements and folklore content for Indonesian language learning. Implications The media can serve as a practical classroom resource for supporting interactive, contextual, and culturally relevant literacy learning in elementary education. Highlights • Developed a folklore based digital learning medium for fourth grade students.• Expert validation showed very valid media and material quality.• Student scores and motivation rose after classroom use. Keywords Digital Pop Up Book; Indonesian Language Learning; Folklore; Learning Motivation; Learning Outcomes